Geothermal Energy Development in Iceland - Mikhaylov, Alexey (International Journal of Energy Economics and Policy, 2020)
The article analyzes the political and legal features of the organization of renewable energy activities in Iceland. It is designed by the relevance of using renewable energy as one of the safest for the environment, natural resources, health and life of the population. The choice of Icelandic legislation in this area is based on 85% of all primary energy of Iceland are renewable sources; a full-fledged legislation has been created in Iceland. The provisions of the National Plan for the Development of Renewable Sources were studied in 2014, which determines the direction of state internal and external energy policy. The basic legislative acts that regulate various aspects of renewable energy development in Iceland: The Law on National Energy Company and the Act of electricity produced using renewable sources. The legal status and competence of state bodies is involved in the process of making and implementing energy relevant decisions in this area, namely: Ministry of Industry and Innovation and National Energy Agency. Keywords: renewable energy, energy law, energy law of Iceland, energy origin guarantee, natural resources, Icelandic politics. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.9047